Strategi Pengelolaan Risiko dan Keamanan Informasi pada Platform E-Bisnis: Studi Kasus Tokopedia: (Tokopedia: Bagaimana Platform Ini Menangani Insiden Kebocoran Data pada Tahun 2020, Termasuk Langkah Mitigasi dan Perbaikan Sistem Keamanannya) - Marsyanada Marsyanada (PUTRA JAWA PUBLISHER, 2024)
The data leak incident experienced by Tokopedia in 2020 is an important reminder of the need for effective risk management and information security strategies on e-business platforms. This article discusses the mitigation measures taken by Tokopedia, including system security enhancements, user education, and collaboration with cybersecurity agencies. Using a qualitative approach through case study analysis, this article reviews the incident chronology, evaluation of mitigation measures, and recommendations for more proactive risk management. The findings show that while Tokopedia's mitigation measures were successful in improving security, further investment in proactive technologies such as two-factor authentication (2FA) and end-to-end encryption is required. The article concludes with recommendations for other e-business platforms to minimize the risk of data leakage and maintain customer trust.